SISTEM INFORMASI AKUNTANSI PERSEDIAAN BARANG BERBASIS KOMPUTER PADA BAGIAN GUDANG DI SEKOLAH CINTA KASIH JAKARTA - Siregar, Saut Aleksius (Infotech: Journal of Technology Information, 2019)
Technology development has a very important role in information management. Processing information related to large and fast inventory flows in a company certainly requires accuracy, efficiency, and effectiveness of information systems. This problem is experienced by the Sekolah Cinta Kasih in the activities of those who still use the manual recording system. The type of research used is descriptive research with a case study approach. By doing a series of system analysis, the author intends to design a computerized inventory information system. The system uses Microsoft Access 2010 which is capable of being operated in a Microsoft Windows XP operating system or a higher version of Windows.The computerized information system is expected to provide various facilities for the warehouse in processing database information and reports that are accurate, fast, and efficient. And minimize errors in inventory control. The new system design aims to prevent errors in the Accounting Information System Inventory by the Cinta Kasih School.